New mixed‐ligand iron(III) complexes containing thiocarbohydrazones: Preparation, characterization, and chemical reactivity analysis through theoretical calculations. (3rd June 2022) - Kaya, Yeliz; Erçağ, Ayşe; Kaya, Savaş; Katin, Konstantin P.; Atilla, Devrim
Abstract : Five new mixed ligand Fe(III) complexes, namely, [FeL1(acac)] (L1Fe), [FeL2(acac)] (L2Fe), [FeL3(acac)] (L3Fe), [FeL4(acac)] (L4Fe), and [FeL5(acac)] (L5Fe), were synthesized from the reaction of iron(III) acetylacetonate with [ONS] donor dibasic tridentate symmetrical bisthiocarbohydrazone ligands. Synthesized mixed ligand Fe(III) complexes were characterized with infrared spectra, UV‐Vis spectra, mass spectra, elemental analysis, magnetic susceptibility measurements, and thermogravimetric analysis. The molar conductance measurement in DMF solution confirmed that the complexes are nonelectrolytic. TGA analysis results showed that the thermal stability of the ligands and complexes was high. Antioxidant capacity and free radical scavenging activity of the mixed ligand Fe(III) complexes were investigated using CUPRAC and the DPPH radical scavenging method. Mixed ligand Fe(III) complexes showed higher antioxidant activity than ligands and reference compound. Popular conceptual density functional parameters like hardness, electrophilicity, dipole moment, and chemical potential for new ligands and their Fe(III) complexes were calculated and discussed. Chemical reactivity and stabilities of the studied chemical systems were analyzed with the help of well‐known electronic structure principles like maximum hardness principle (MHP), hard and soft acid–base (HSAB) principle, minimum polarizability principle, and minimum electrophilicity principle. L1Fe, which has the highest chemical hardness value, is the most stable complex according to MHP. Abstract : New mixed ligand Fe(III) complexes were prepared and characterized. Fe(III) complexes are found to possess higher antioxidant activity than the free ligands and showed very good free radical scavenging activity. Quantum chemical calculations based on the density functional theory were made.